Mengkritisi Asas-asas Hukum Acara Perdata - busyro muqoddas (Jurnal Hukum IUS QUIA IUSTUM, 2002)
The critical thinking on civil law procedure must be put on the frame and spectrum of comprehensive thinking, namely how is the role of judicative body on the more basic agenda, namely to give the contribution for civil conflict solution, to recover and distribute right and responsibility proporsionally. It also recovers the public balance, give law pro tection for individual through considering public right andinterest